From low emission zone to academic track: Environmental policy effects on educational achievement in elementary school - Johannes Brehm; Nico Pestel; Sandra Schaffner; Laura Schmitz (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Low Emission Zones (LEZs) reduce local air pollution by restricting emission-intensive vehicles from accessing designated areas and have been shown to improve population health. Little is known about the effects of driving restriction policies on other areas of life. This paper studies the effects of LEZs on the educational achievements of elementary school students in Germany, measured by secondary-school transition rates. Using school-level data from North-Rhine Westphalia (NRW), Germany's largest federal state, we exploit the staggered adoption of LEZs since 2008 in a difference-indifferences framework. Our results imply that LEZs increased rates of transition to the academic track by 0.9-1.6 percentage points in NRW. Our findings on the district level for all of Germany confirm the external validity of these findings. Using geo-referenced data from the German Socio-Economic Panel, we provide suggestive evidence that a reduction in the prevalence of respiratory infections is a vital channel through which LEZs affect schooling outcomes. – – Umweltzonen verringern die lokale Luftverschmutzung, indem sie emissionsintensive Fahrzeuge von der Zufahrt zu den ausgewiesenen Gebieten abhalten und nachweislich die Gesundheit der Bevölkerung verbessern. Über die Auswirkungen von Fahrverboten auf andere Lebensbereiche ist wenig bekannt. Dieses Papier untersucht die Auswirkungen von Umweltzonen auf die schulischen Leistungen von Grundschülern in Deutschland, gemessen an den Übergangsquoten in die weiterführenden Schulen. Unter Verwendung administrativer Schuhldaten aus Nordrhein-Westfalen (NRW), dem größten deutschen Bundesland, nutzen wir die gestaffelte die gestaffelte Einführung von Umweltzonen seit 2008 in einem Differenz-in-Differenzen Ansatz. Unsere Ergebnisse deuten darauf hin, dass die Einführung von Umweltzonen die Übergangsraten auf das Gymansium in NRW um 0,9-1,6 Prozentpunkte erhöhen. Unsere Ergebnisse auf Kreisebene für ganz Deutschland bestätigen die externe Validität dieser Befunde. Analysen basieren auf dem georeferenzierten Sozio-ökonomischen Panel (SOEP) deuten zudem darauf hin, dass eine Verringerung der Prävalenz von Atemwegsinfektionen ein wichtiger Kanal ist, über den die Umweltzonen die schulischen Ergebnisse beeinflussen.
Keywords: I21; J24; Q52; Q53; Q58; 330; Low emission zone; education; air quality; Germany